Supervision of Scientific and Engineering Personnel - R.C. (Relations Industrielles / Industrial Relations, 1957)
The article reviews the booklet, "Supervision of Scientific and Engineering Personnel," compiled by John T. Lloyd and Robert D. Gray. Published by the Industrial Relations Section, California Institute of Technology, Bulletin No. 26 (82 pp.).